Penguatan Ekonomi Lokal Melalui Rebranding UMKM Mencalok di Kampung Kelam Pagi - Juria Angraini; Rindi Apriliani Utami; Bunga Afrilia Dewi Asih; Shiwy Wulandari; Tiara Damar Sita; Ariel Suryadi Siregar; Noni Permata Susanto; Ronaldo Simbolon; Nurmeiza Nurmeiza; Machoman Machoman; Dios Sarkity (Jurnal Pengabdian Masyarakat Waradin, 2025)
The Community Service Program (KKN) in Kampung Kelam Pagi, Tanjungpinang City, focused on strengthening Mencalok MSMEs through a rebranding strategy. A participatory approach was used to engage the community at every stage, from observation, planning, and implementation to evaluation. The activities included the creation of a new logo, product packaging improvements, and the facilitation of Business Identification Number (NIB) registration for MSME actors. The results showed significant improvements in the product's visual identity, business legality, and market value of Mencalok in local and regional markets. Rebranding also provided additional benefits, such as legal recognition, access to government programs, financing opportunities, and the promotion of traditional culinary culture. The program empowered women by enhancing their managerial skills and fostering economic independence. In addition to these efforts, digital marketing strategies were introduced, helping the MSMEs reach a broader audience and improve their online presence. Product diversification was also recommended to strengthen competitiveness and ensure long-term business sustainability. These findings highlight that rebranding is not merely a visual change but a strategic tool that enhances the economic, social, and cultural value of traditional MSMEs. By integrating modern business practices with local cultural heritage, this initiative not only improved business outcomes but also contributed to the preservation and promotion of regional traditions.